VD_FINDINFO Décision / 2014 / 586 vom 7. Juli 2014 - VD Tribunal cantonal (2014)
EXPERTISE PSYCHIATRIQUE, PREUVE ILLICITE | 141 al. 2 CPP (CH), 141 al. 5 CPP (CH), 184 CPP (CH), 185 CPP (CH), 187 CPP (CH)